Enhanced cyclability of elastocaloric effect in boron-microalloyed Ni-Mn-In magnetic shape memory alloys. (1st April 2017) - Yang, Z.; Cong, D.Y.; Sun, X.M.; Nie, Z.H.; Wang, Y.D.
Abstract: Cyclability of elastocaloric effect is of crucial importance for practical applications of elastocaloric refrigeration which is a promising alternative to the conventional cooling technology based on vapor compression. The well-known Ni-Mn-based magnetic shape memory alloys exhibit fascinating multicaloric effects (including elastocaloric, magnetocaloric and barocaloric effects), but they are intrinsically brittle because of weak grain boundary cohesion, which results in poor cyclic stability of elastocaloric effect. Here we demonstrate that microalloying with boron is very effective in enhancing the mechanical properties and cyclic stability of elastocaloric effect in Ni-Mn-In intermetallic magnetic shape memory alloys. The elastocaloric effect of the boron-free Ni51.5 Mn33 In15.5 alloy degrades rapidly after only ∼20 cycles; in contrast, that of the boron-doped (Ni51.5 Mn33 In15.5 )99.7 B0.3 alloy remains stable with almost no degradation for more than 150 cycles. The enhancement of mechanical properties and cyclic stability of elastocaloric effect is mainly attributed to the increase of gain boundary cohesion and grain refinement resulting from microalloying with boron. Furthermore, by virtue of its enhanced mechanical properties, a high adiabatic temperature change up to 6.6 K (under 550 MPa), a large stress-induced entropy change of 20.0 J kg −1 K −1 (under 300 MPa) and a high coefficient of performance of 18 were successfully achieved in the boron-doped (Ni51.5 Mn33 In15.5 )99.7 B0.3 alloy showing a working temperature just around room temperature. These advantages make this alloy promising for room-temperature elastocaloric refrigeration. This study is instructive for designing high-performance elastocaloric materials for solid-state mechanocaloric cooling applications. Graphical abstract: Image 1